The association between motor blockade and duration of second stage of labor with labor epidural analgesia: A retrospective cohort study - Daryl Jian An Tan; Rehena Sultana; Chin Wen Tan; Ban Leong Sng (Bali Journal of Anesthesiology)
Abstract Background: Studies have suggested that epidural analgesia could increase the duration of second stage of labor associated with motor blockade. However, current literature is limited on specific parturients mostly affected by motor blockade. Objective: We aimed to determine the associations between motor blockade and duration of second stage of labor according to the mode of delivery in parturients receiving labor epidural analgesia. Materials and Methods: A retrospective cohort study was conducted using labor epidural analgesia records from parturients who delivered vaginally: normal vaginal delivery (NVD) and instrument-assisted delivery (instrumental delivery). Motor block was categorized into: no motor block and any degree of motor blockade (modified Bromage score of 1 to 3). Zero-inflated Poisson regression model for duration of second stage of labor and logistic regression model for presence of motor blockade was used for data analysis. Results: Data from 8420 parturients showed that parturients with instrumental delivery, in the presence of motor blockade, were more likely to have longer duration of second-stage labor (P = 0.0131), but parturients with NVD were more likely to have a shorter duration (P = 0.0005). Univariate analysis suggested that parturients with NVD associated with motor blockade had higher incidences of post-procedure neural deficit (P = 0.0064) 24 to 48 h postdelivery. However, this relationship was not found in instrumental delivery. Conclusion: Instrumental delivery had positive associations between presence of motor blockade and duration of second-stage of labor, while NVD had positive associations between presence of motor blockade and post-procedure neural deficit. Future research could be important to further refine these associations in the aforementioned parturient groups.